Riesgo de entrada de la enfermedad de Newcastle en España a través de columbiformes - Iglesias Martín, I.; Martínez Avilés, M.; De la Torre Reoyo, A.; Sánchez-vizcaíno Rodríguez, Jm. (Revista Complutense de Ciencias Veterinarias, 2008)
Newcastle disease is a disease of major importance for poultry and wild birds. Wild birds order columbiformes can act in the spread of the disease, we performed a qualitative risk assesment of disease introduction into Spain by columbiformes migrations. The following factors have been introduced in the model: the Spanish provinces at with the columbiformes arrive and countries of the departure, Newcastle incidences in the in the countries of the departure, the distribution of sedentary columbiformes in Spain by provinces and the spanish avian production density. The final result offer a first descriptive analysis of the situation relating to the risk of introduction of Newcastle by migrating columbiformes birds, allowing to assess the importance of each factor.